The crime of embezzlement of public funds and the appropiation of “representation expenses” of the Congress - Chanjan Documet, Rafael (2019)
This article discusses whether the collection and non-return of “representation expenses” by Congressmen of the Republic of Peru may result in criminal liability for the crime of embezzlement of public funds when they do not do correctly the representation activity, since it would be a monetary amount that constitutes a public funds that has been entrusted to the public official for his administration by reason of his office. In this regard, the legal nature of “representation expenses” will also be analyzed in order to argue that they are in fact “travel expenses” who must be duly regularized.